Solvent concentration effect on antioxidant activity and total phenolic content of Malaysian herbs - Nurul Atikah, Mohd Nazir (2016)
Generally, herbal plants that are relatively abundant sources of antioxidant compounds with high antioxidant activities have been consume for thousands of century by world population (Amin et al., 2004, 2006; Amin & Lee, 2005). The objective of this research was to determine total phenolic content, antioxidant activities of Malaysian herbal plants. The potential of using herbal Pandanus amaryllifolius (PA), Sauropus androgynous (SA) and Persicaria odorata (PO) as a natural antioxidant for food applications were investigated. Total phenolic content (TPC) of herbs was determined using Folin-Ciocalteau reagent assay and antioxidant activity were analyzed by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity. The determination of TPC and antioxidant activity was done for each plant extract by using ethanol as solvent, different concentration of ethanol aqueous solutions, including 95%, 75%, 50%, 25% and 0%. Different concentration of extraction solvents significantly affected the TPC of all samples. 75% ethanol extract of Persicaria odorata (PO) exhibited the highest TPC with 6.0910 mg GAE/L extract sample. Highest antioxidant activity is also obtained by 75% ethanolic extract of PO; however all plants showed positives correlation between TPC and DPPH assay. In conclusion, all herbs exhibit the potential sources of natural antioxidant that can be used as functional food in food industry.